2022
DOI: 10.4103/jfmpc.jfmpc_957_22
|View full text |Cite
|
Sign up to set email alerts
|

Family support and well-being programme (FSWP): A specialized family strengthening psychosocial services for parents of children in conflict with law

Abstract: A BSTRACT Background: A multidimensional family support and well-being programme (FSWP) was initiated to support the families of children in conflict with law (CICL) and strengthen their participation in the integration process. This programme aims to successfully reintegrate children into the family and build parental capacity to manage them. This study presents the overview of the multidimensional FSWP initiated in an observation home, facility for CICLs, Bengaluru, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Importantly, due to diverse interactions with peers actions, urban deprivation and equivalent shortage, lack of discipline, parental surveillance, and the accessibility of using illegal methods, most children have families with drug consumption, physical or sexual abuse, divorce, separation, and psychological disorders. Uneven parenting and poor monitoring also contribute to adolescent criminality (Ganie et al, 2022).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Importantly, due to diverse interactions with peers actions, urban deprivation and equivalent shortage, lack of discipline, parental surveillance, and the accessibility of using illegal methods, most children have families with drug consumption, physical or sexual abuse, divorce, separation, and psychological disorders. Uneven parenting and poor monitoring also contribute to adolescent criminality (Ganie et al, 2022).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Manuel (2019) suggested that educational programs can prevent these children from committing crimes if they can either finish their studies or finish at least High School Level, and thus, they can find a more decent job. However, 37.13% of respondents answered that any family members had a history of imprisonment, highlighting the potential impact on the children's behaviour (Jangam et al, 2022), and they can be more likely to engage in illegal activities.…”
Section: Figure 1 Educational Qualification Of Respondentsmentioning
confidence: 99%